Tinjauan Yuridis Tentang Penolakan Uang Logam Sebagai Alat Pembayaran dalam Transaksi Jual Beli oleh Pelaku Usaha (Kios) Ditinjau dari Undang-Undang Nomor 7 Tahun 2011 Tentang Mata Uang di Pasar Oeba Kelurahan Fatubesi Kecamatan Kota Lama Kota Kupang - Abdullah Putra Nogo Mbele; Siti Ramlah Usman; Helsina Fransiska Pello (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to determine the factors that cause business actors (kiosks) to reject coins as a means of payment in sale and purchase transactions at Oeba Traditional Market, Fatubesi Urban Village, Kota Lama Subdistrict, Kupang City and the legal consequences of such rejection in terms of Law Number 7 of 2011 concerning Currency. The benefits of this research are to provide information and knowledge that enriches the study of law and as a consideration or input for the government and information for the community. This research is a type of empirical legal research. The results of this study show: (1) The factors causing business actors (kiosks) in Oeba Traditional Market to reject coins with denominations of Rp200.00 and Rp100.00 as a means of payment in sale and purchase transactions are community perception factors, refund factors, and practicality factors. (2) The legal consequences of this rejection in terms of Law Number 7 of 2011 concerning Currency are that the sale and purchase agreement can be cancelled because there is no agreement between the parties and the business actor (kiosk) can be punished. The conclusions of this study are (1) The factors causing business actors (kiosks) in Oeba Traditional Market to reject coins with denominations of Rp200.00 and Rp100.00, namely the public perception factor, the refund factor, and the practicality factor. (2) The legal consequences of the rejection are that the sale and purchase agreement can be cancelled and the business actor (kiosk) can be punished. Suggestions from the author are, for the government, it is expected to be more aggressive in conducting socialisation about money and for business actors (kiosks) and the public are expected to treat money properly.